The assessment of landslides disaster mitigation in Java Island, Indonesia: a review - Akhmad Zamroni; Ayu Candra Kurniati; Haris Nur Eka Prasetya (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
The frequency of landslides and the fact that a large number of people live in the landslides-prone areas lead to a high death toll in Java Island, Indonesia – over 1,112 people in the period between 1999 and 2005. Indonesian National Disaster Management Agency (Badan Nasional Penanggulangan Bencana [BNPB]) reported 2,766 landslides that occurred in Java from 2014 to 2019, with 662 deaths. From its state, it looks as if Indonesia 's disaster mitigation is still weak. It is very essential to a deep understanding of landslides disaster mitigation weakness in Indonesia with the approach of governments, researchers, and local communities action. This research is a review of landslides disaster mitigation in Java Island with the approach of governments, researchers, and local communities action. Furthermore, the purpose of this study is to highlight the driving forces of landslides disaster mitigation in Java Island, Indonesia. From the assessment of each stakeholder (government, researchers, and local communities), the driving forces of landslides disaster mitigation in Java Island are the central government has commanding disaster management activities to local governments. However, the implementation of landslides disaster mitigation at the regional level has some obstacles such as the lack of residential development planning.Many landslide research results have only become scientific papers but the landslides-prone areas have not been fully paid attention by the local government such as the absence of landslide danger warning signs.In addition, the level of preparedness and awareness among local communities is not constant at any given time. Usually, community preparedness levels can be high following a disaster. It is likely, however, to diminish over time.